Rationale in Forum Discussions as Support for Software Upgrading of Online Course Platforms - Clementino, Tiago L. P.; Moura, José Antão B. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2019)
In online course software platforms, the forum may be an important instrument for feedback on pedagogical aspects. Students' and instructors' evaluations spontaneously shared in the forum - in terms of criticism, recommendations, or requests - may also regard the platform's software tools. These evaluations resemble what is called 'rationale', a useful concept from Software Engineering. This paper presents an exploratory study about mining spontaneous user rationale in Massive Open Online Course forum discussions. Results provide qualitative evidence that rationale can be an instrument to collect requirements for the evolution of support software in online educational platforms.